Factors Associated with Timeliness of Surgical Repair among Infants with Myelomeningocele: California Perinatal Quality Care Collaborative, 2006 to 2011 - Kancherla, Vijaya; Ma, Chen; Grant, Gerald; Lee, Henry C.; Shaw, Gary M.; Hintz, Susan R.; Carmichael, Suzan L. (American Journal of Perinatology, 2019)
Objective This study aimed to examine factors associated with timely (0–2 days after birth) myelomeningocele surgical repair.Study Design We examined 2006 to 2011 births from the California Perinatal Quality Care Collaborative, linking to hospital discharge and vital records. Selected maternal, infant, and delivery hospital characteristics were evaluated to understand disparities in timely repair. Poisson regression was used to estimate adjusted risk ratios (aRRs) and 95% confidence intervals (CIs).Results Overall, 399 of the 450 (89%) infants had a timely repair and approximately 80% of them were delivered in level III/IV hospitals. Infants with hydrocephalus were significantly less likely to have a delayed myelomeningocele repair compared with those without (aRR = 0.22; 95% CI = 0.13, 0.39); infants whose medical care was paid by Medi-Cal or other nonprivate insurance were 2.2 times more likely to have a delayed repair compared with those covered by a private insurance (aRR = 2.23; 95% CI = 1.17, 4.27). Low birth weight was a significant predictor for delayed repair (aRR = 2.06; 95% CI = 1.10, 3.83).Conclusion There was a significant disparity in myelomenigocele repair based on medical care payer. Families and hospitals should work together for timely repair in hospitals having specialized multidisciplinary teams. Findings from the study can be used to follow best clinical practices for myelomeningocele repair.
Keywords: health care; disparities; myelomeningocele; open spina bifida; pediatric; surgery; spina bifida; timeliness